2022
DOI: 10.1002/adma.202201630
|View full text |Cite
|
Sign up to set email alerts
|

2D Transition Metal Dichalcogenide with Increased Entropy for Piezoelectric Electronics

Abstract: Piezoelectricity in 2D transition metal dichalcogenides (TMDs) has attracted considerable interest because of their excellent flexibility and high piezoelectric coefficient compared to conventional piezoelectric bulk materials. However, the ability to regulate the piezoelectric properties is limited because the entropy is constant for certain binary TMDs other than multielement ones. Herein, in order to increase the entropy, a ternary TMDs alloy, Mo1−xWxS2, with different W concentrations, is synthesized. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…This method is commonly employed for investigating piezoelectric properties in various two-dimensional materials. 50,51 Based on the principles of quantum mechanics, this method can be used to prove the polarization change DP in solids, because the adiabatic change is calculated using the Kohn-Sham Hamiltonian quantity, and can also be approximated using the original electron wave function. 52 The parallel piezoelectric coefficient e 11 and the vertical piezoelectric coefficient e 31 are obtained by changing the electric dipole moment in the x-direction and the z-direction with respect to the biaxial strain applied in the x-direction, respectively.…”
Section: Piezoelectricitymentioning
confidence: 99%
“…This method is commonly employed for investigating piezoelectric properties in various two-dimensional materials. 50,51 Based on the principles of quantum mechanics, this method can be used to prove the polarization change DP in solids, because the adiabatic change is calculated using the Kohn-Sham Hamiltonian quantity, and can also be approximated using the original electron wave function. 52 The parallel piezoelectric coefficient e 11 and the vertical piezoelectric coefficient e 31 are obtained by changing the electric dipole moment in the x-direction and the z-direction with respect to the biaxial strain applied in the x-direction, respectively.…”
Section: Piezoelectricitymentioning
confidence: 99%
“…The widely used precursors for spin-coating, such as Na 2 MoO 4 , Na 2 WO 4 , (NH 4 ) 2 MoO 4 , and (NH 4 ) 2 WO 4 , are neutral or acidic when dissolved in water. 12,[17][18][19][20][21]23 The effects of acidity and alkalinity of the precursor solution on the results of synthesis have seldom been studied.…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have developed multiple strategies for synthesizing lateral heterojunctions, such as lithographically assisted method, , two-step growth method, , one-pot multistage growth method, and spin-coating method. , The spin-coating method is an important method to synthesize Mo x W 1– x S 2 ternary alloys and MoS 2 /WS 2 lateral heterojunctions. Using this method, Mo x W 1– x S 2 ternary alloys were synthesized by spin-coating sources on the substrate, which will be segregated as nanoparticle precursors and then sulfurized. However, the formation of ternary alloys should be avoided when MoS 2 /WS 2 lateral heterojunctions with a sharp boundary were expected to be synthesized, which requires precise design of the experimental process. ,, The main methods include the temporal and spatial separation of the two precursor sources. The method based on spatial separation is to place two precursor sources at different locations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the TMDCs, alloys with five transition-metals have the highest entropy of mixing (−1.6 RT , where R is the universal gas constant), thereby suggesting an entropically stabilized configuration; density functional theory (DFT) calculations , coupled with experiments of selected group 5 and 6 cation compositions revealed that although some of the ternary alloys are unstable, high-entropy alloy (HEA) TMDCs are stable with superior thermal, electrochemical, and electronic characteristics. HEA TMDCs are attractive for applications in energy storage and harvesting, , in electrocatalysis, , as sensors, and more. , DFT calculations of 126 equiatomic transition-metal alloy disulfides each with five group 4–6 metals predicted that these compounds are thermodynamically stable at temperatures between 130 and 1200 K. Current approaches ,, for the synthesis of HEA TMDC layers rely on exfoliation from a polycrystalline bulk prepared from powder precursors. The ability to synthesize TMDC alloys of desired composition and layer thickness expands the available functionalities for a variety of applications.…”
mentioning
confidence: 99%